DESIGNING AN INCLUSIVE BUSINESS INCUBATOR MODEL TO FOSTER ENTREPRENEURIAL COMPETENCE AMONG VOCATIONAL HIGH SCHOOL STUDENTS - Dwi Anggraeni; Budiyanto; Erny Roesminingsih; Nunuk Hariyati; Amrozi Khamid (Academic Journal Research, 2026)
Objective: The gap between the competencies of Vocational High School (SMK) graduates and the needs of the job market, as well as the limited entrepreneurial mentoring services for students with special needs, drives the need for an inclusive entrepreneurship development model in vocational education. This research aims to develop an Inclusive Business Incubator Model for Vocational High Schools (SMK) that combines the Teaching Factory (TeFa) concept with the business incubator concept of Higher Education institutions, as well as to test its feasibility, practicality, and effectiveness. Method: The research uses a research and development (R&D) approach by adapting six out of the ten stages of the Borg and Gall model, including preliminary study, planning, initial product development, initial trial, product revision, and main field trial. The trial was conducted at SMK Negeri 1 Probolinggo as the main location and disseminated at SMK Negeri 3 Probolinggo and SMK Swasta A. Yani Probolinggo. Data were collected thru interviews, documentation, and Likert scale questionnaires from expert validators, practitioner validators, users, and industry mentor tenants, and then analyzed descriptively both quantitatively and qualitatively. Results: The research results show that the Inclusive Business Incubator Model for Vocational High Schools meets the very feasible criteria with an average feasibility percentage of 89.6%, the implementation guidebook meets the very practical criteria with a percentage of 86.98%, and the model is considered effective with a percentage of 84.3% based on the target, resource, internal process, and integrated approaches, as well as 87.6% based on the organizational effectiveness approach. Novelty: These findings indicate that the Inclusive Business Incubator in Vocational High Schools is associated with strengthening the entrepreneurial readiness of students, including those with special needs, and has the potential to be adopted as a strategic platform for inclusive entrepreneurship education at the vocational education level.